Cardiac Valve Replacement in Patients Over Sixty—A Report of Ten Operations with One Death - Roe, Benson B. (1966)
Of 85 patients who underwent cardiac valve replacement, 10 were 60 or more years old. Nine of the 10 lived, and the excellent results confirmed that advanced age does not contraindicate major corrective operations.